Analysis of Urinary Endothelin-I Levels in Obese Late Adolescents - Dian Fahmi Utami; Irfan Idris; Arsyadi Arsyad; Ika Yustisia; A. Aryandi; Husni Cangara (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
Obesity is a health problem that often occurs in late adolescents and early adults. Endothelial damage that occurs in obese people can cause increased production of endothelin-1. This study compares urinary endothelin-1 levels in the obese and normal groups. It used analytical research methods with a quantitative approach to collect and measure data in numbers. The study design was cross-sectional by comparing endothelin-1 levels in normal and obese adolescent groups. This research was conducted in Makassar City from April to June 2022. The study population was obese and non-obese people in their late teens and early adulthood. The sample collection technique used in this study is a purposive sampling technique, which is a non-random sampling technique. The number of samples in the study for the Obese group was 26, while in the Normal group was 26. The analysis used the Independent Sample T Test statistical test. The results showed that the average urinary endothelin I level in the obese group was 40,930 ng/l, and in the normal group, 55,547 ng/l. Which shows a significant difference in average endothelin I levels (p<0.05) between the obese and normal groups.